1997
DOI: 10.1007/pl00005666
|View full text |Cite
|
Sign up to set email alerts
|

Scopolamine increases prehensile force during object manipulation by reducing palmar sweating and decreasing skin friction

Abstract: The aim of this study was to determine whether relatively long-term changes in skin friction induced by a pharmacological blockade of sweat excretion would alter the grip forces applied to objects of a variety of different surface textures and frictions. Five men and three women were asked to lift the vertically mounted armature of a linear motor between the thumb and index finger and to hold it against an opposing force for 2 s. A 1.0-kHz tone indicated to the subject that the manipulandum had been correctly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Zackrisson et al [61] have measured grip coefficients of friction for hyperhidrosis patients, and shown that treatment to reduce sweat rates by botulinium toxin injections both affects the friction and can alleviate grip problems; in fact, the anhidrosis due to the injections tended to reduce the friction to levels expected for relatively dry skin. Smith et al [62] have shown that similar reductions in friction occur in grip experiments involving smooth surfaces when anhidrosis is induced by scopolamine injections.…”
Section: Participantmentioning
confidence: 89%
“…Zackrisson et al [61] have measured grip coefficients of friction for hyperhidrosis patients, and shown that treatment to reduce sweat rates by botulinium toxin injections both affects the friction and can alleviate grip problems; in fact, the anhidrosis due to the injections tended to reduce the friction to levels expected for relatively dry skin. Smith et al [62] have shown that similar reductions in friction occur in grip experiments involving smooth surfaces when anhidrosis is induced by scopolamine injections.…”
Section: Participantmentioning
confidence: 89%
“…Up to now, various studies have considered the importance of the skin hydration level on performance during object manipulation. Smith et al (1997) investigated the influence of scopolamine on the prehensile force during object manipulation and showed an increase of this force due to a reduction of palmar sweating. In the same way, Zackrisson et al (2008) reported that a significant decrease of the CF and consequent significant increase of the grip force were observed when patients with very high sweating rate (hyperhidrosis) manipulated objects.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of sweat in determining the friction of the finger pad has been observed in a number of studies. Smith et al [77] described the results of applying scopolamine patches to subjects in order to suppress palmar sweating by blocking the muscarinic receptors of the eccrine sweat glands. On the basis of grip experiments it was found that, for some of the surfaces examined, there was an increase in the peak and static grip forces, which was interpreted as a response to an increase in the slipperiness of the skin.…”
Section: Occlusionmentioning
confidence: 99%